Boundedness dan Polusi pada Situs Islam Cirebon Abad XVI-XVIII - Johan, Irmawati M. (Wacana, Journal of the Humanities of Indonesia, 2007)
Archaeological sites are the traces of people 's lives in the past. The remaining traces are texts, simply waiting to be read. This article tries to interpret the housing patterns in the sites of palaces in Cirebon using the concepts of boundedness, the sacred, the profane, and the pollution.